Revolutionizing Dermatology: The Use of Computer Vision for Automated Skin Lesion Analysis - Secara, Ion-Alexandru; Hordiiuk, Dariia (British Journal of Healthcare and Medical Research, 2024)
The integration of computer vision in dermatology holds promise for revolutionizing skin lesion analysis. This article offers a comprehensive exploration of the current challenges in skin lesion analysis, the potential of computer vision in dermatology, methods and algorithms in skin lesion analysis, the impact of computer vision on dermatology, its respective limitations and future directions. Additionally, the article includes a review of existing literature and original analysis. The potential of computer vision in dermatology is discussed, emphasizing its capacity to enhance diagnostic accuracy, reduce human error in dermatological assessments, and provide faster and more accessible analysis. Furthermore, the potential of computer vision in dermatology extends beyond diagnostic applications, with the ability to comply with stricter data privacy protection laws and facilitate the development of visual object detection platforms powered by federated learning, ensuring data privacy and security in dermatological applications. The article concludes with a summary of key findings, implications for the field of dermatology, and recommendations for future research.